If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2X + -1(5X + 9) = 8 + -3X Reorder the terms: 2X + -1(9 + 5X) = 8 + -3X 2X + (9 * -1 + 5X * -1) = 8 + -3X 2X + (-9 + -5X) = 8 + -3X Reorder the terms: -9 + 2X + -5X = 8 + -3X Combine like terms: 2X + -5X = -3X -9 + -3X = 8 + -3X Add '3X' to each side of the equation. -9 + -3X + 3X = 8 + -3X + 3X Combine like terms: -3X + 3X = 0 -9 + 0 = 8 + -3X + 3X -9 = 8 + -3X + 3X Combine like terms: -3X + 3X = 0 -9 = 8 + 0 -9 = 8 Solving -9 = 8 Couldn't find a variable to solve for. This equation is invalid, the left and right sides are not equal, therefore there is no solution.
| 1+6(x-4)=2-8(x-9) | | (x-6)/4=20 | | 4(4+4k)=-32+8k | | -297=4+7(-5v-8) | | 10+2-21=0 | | x-6/4=20 | | ((T^2+3t-8)-(t^2-2t+6))(t-4)=0 | | 7+20x+12x= | | 3-9t=-10t | | 4X+48=8(X+6)-4X | | 252=4(-1-8v) | | -3-8p=-9p+6 | | 3a+3=9+a | | 4x-3(4-3x)=5(x-4)-40 | | Y/3=40 | | 17/6=34/x | | 2+3(x+5)=38 | | 154=7(7k+1) | | -4(n-6)=n+6 | | 5+8(x-3)=4-4(x-3) | | 4(3Z-1)-5(Z+4)=5(Z+1) | | 2/3=1/9(27) | | -27a-42=a+98 | | T/0.16=0.5/0.4 | | 110=7p-8(2-7p) | | 4(5x-4)=4x+17 | | -3-8=-9+6 | | 162=-6(1-7x) | | 19/11=q/15 | | C+212=-5c-28 | | 6s-8=1+5s | | 8(7n-4)=-480 |